O Fantástico em Edgar Allan Poe e Machado de Assis : um estudo comparado - Esteves, Maylah Longo Gonçalves Menezes (Universidade Federal de São Carlos, 2017)
The goal of the dissertation is the comparison of fantastic tales of the romantic writer Edgar Allan Poe (1809-1849) and the Brazilian writer, who also produced stories of the fantastic genre, Machado de Assis (1839-1908). The predominant issue is how the two authors who lived in different eras and in different countries so diverse socioeconomically may have their supernatural works compared. To answer this disturbing question, some clues of Poean influence on the fantastic tales from the Brazilian writer were obtained, such as the celebrated translation of Poe's poem "The Raven" (1845), made by Machado (or "O Corvo", as translated by himself in 1883); it is also important to our studies to analyse the quotes in newspapers in which Machado wrote, such as o Diário do Rio de Janeiro (1866) and Gazeta de Notícias (1895), as well as the comparison between the short stories “O Espelho” (1882) and “Sem olhos” (1876), by the Brazilian writer, and “William Wilson” (1839) and “Ligeia” (1838), by Poe.
Keywords: O Fantástico na literatura; Literatura comparada; Assis, Machado de, 1839-1908; Fantastic, The, in literature; Literature, Comparative; Poe, Edgar Allan, 1809-1849; LINGUISTICA, LETRAS E ARTES::LETRAS